Type VI secretion system sheath inter‐subunit interactions modulate its contraction - Brackmann, Maximilian (EMBO Rep, 2017)
Secretion systems are essential for bacteria to survive and manipulate their environment. The bacterial type VI secretion system (T6SS) generates the force needed for protein translocation by the contraction of a long polymer called sheath. The sheath is a six‐start helical assembly of interconnected VipA/VipB subunits. The mechanism of T6SS sheath contraction is unknown. Here, we show that elongating the N‐terminal VipA linker or eliminating charge of a specific VipB residue abolishes sheath contraction and delivery of effectors into target cells. Mass spectrometry analysis identified the inner tube protein Hcp, spike protein VgrG, and other components of the T6SS baseplate significantly enriched in samples of the stable non‐contractile sheaths. The ability to lock the T6SS in the pre‐firing state opens new possibilities for understanding its mode of action.